Tratamento de efluente de indústria têxtil utilizando processos químicos avançados via reações de fenton modificadas - Almeida, Alcione Aparecida de (2013)
This study was to evaluate the modified Fenton reactions (RFM), through the addition of six complexing organic separately in each reaction, these being: ascorbic acid (AA), citric acid (CA), ethylenediaminetetraacetic acid (EDTA), gluconic acid (AG), oxalic acid (OA) and tartaric acid (TA), the degradation of textile effluent under varying molar ratios between the total organic carbon, [Fe2+], complexing and [H2O2]. In RFM and Fenton reactions (RF) reactor was used consisting of a borosilicate beaker with a maximum volume of 250 mL, in batch, open, without stirring under room temperature in the optimization phase of time aliquots were removed in the effluent times: 0, 3, 6, 9, 12, 15, 18, 21 and 24 h. The procedure consisted of addition of 250 mL of textile effluent to the reactor for RF and RFM, followed by the oxidant and a catalyst for the RF and oxidizing catalyst and complexing to RFM. RF best results in reduction of TOC was obtained in 12 h treatment under initial pH value of 3.0 and a molar ratio [1:0,9:27,5]. Concerning the [COT:Fe2+:H2O2] where noted a reduction of 91.06% of TOC, COD 94.51%, 99.88% and 99.02% of the turbidity of discoloration. The RFM showed the best results with the use of complexing GA at 15 h of treatment under molar ratio [1:1,31:1,12:27,94], its [COT:Fe2+:AG:H2O2] which promoted reduction of 82.30% of TOC, COD 90.53%, 99.27% and 99.19% of the turbidity of discoloration, TA had similar results in reduction of parameters when the effluent subjected to 12 h of treatment in a molar ratio [1:0,76:0,94:32,13]. Concerning the [COT:Fe2+:AT:H2O2] under these conditions was possible to reduce 75.05% TOC, 94.89% COD, 97.84% turbidity and discoloration of 96.75%. However, RF are effective in the treatment of textile effluents, though the RFM presented as a new possibility of the treatment without the necessity of adjusting the initial pH value.